POLA PERTUMBUHAN KEPITING BAKAU (Scylla serrata, Forskal 1775) YANG TERTANGKAP BUBU DI SUNGAI SANRANGANG, SULAWESI SELATAN - Wayan Kantun; Warda Susaniati; Muhammad Alwi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
The local community has caught mud crabs for years and increased fishing pressures, leading to biological structure changes. Accordingly, studying the growth pattern, condition factors, and structure of mud crab in the Sanrangang River, Takalar Regency, South Sulawesi Province is necessary. This research was conducted from June to August 2020 in the Sanrangang River, Takalar Regency, South Sulawesi Province. This study compared the efficiency and effectiveness of three types of bubu, namely folding bubu, rakkang and wheel bubu based on the experimental fishing by using tilapia as the bait. Data were analyzed by Chi-Square non-parametric test. Results showed that the catch of mud crabs for folding bubu, rakkangs, and wheel bubu was 120; 107; and 110 species. The width and weight of mud crabs’ carapace caught by each bubu were as follows: from folding bubu ranged from 34.07 to 99.02 mm (60.34 ± 15.06 mm) and 21.62 to 389.57 g (92.41 ± 75.38 g); rakkang ranged from 35.09 to 98.51 mm (66.91 ± 13.95 mm) and 21.94-297.29 g (87.86 ± 34.35 g) and wheel bubu ranged from 34.21- 98.11 mm (66.32 ± 16.83 mm) and 22.01-485.45 g (102.17 ± 79.87 g). The growth patterns of the catch from all gear were negative allometric. The condition factors of folding bubu, rakkangs, and wheel bubu ranged from 0.40631-2.3998, 0.4598-2.4553 and 0.4962-3.1098 respectively. The gear producing the highest weight and the best condition factor was wheel bubu. Keywords: Condition factor, mud crab, size structure, growth type.